2004
DOI: 10.1111/j.1538-7836.2004.00986.x
|View full text |Cite|
|
Sign up to set email alerts
|

Prophylactic and perioperative replacement therapy for acquired factor XIII deficiency: a rebuttal

Abstract: To cite this article: Ajzner É , Muszbek L. Prophylactic and perioperative replacement therapy for acquired factor XIII deficiency: a rebuttal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…In addition, antigen testing can provide another estimation of FXIII levels. It is particularly useful for quantitative analysis of patients with low FXIII levels, because the Berichrom â assay has been suggested to overestimate FXIII activity at the low range [20]. In our study, FXIII activity and antigen showed high concordance, especially at higher levels, suggesting that protein measured by the ELISA assay was fully functional, similar to previously published findings [11].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, antigen testing can provide another estimation of FXIII levels. It is particularly useful for quantitative analysis of patients with low FXIII levels, because the Berichrom â assay has been suggested to overestimate FXIII activity at the low range [20]. In our study, FXIII activity and antigen showed high concordance, especially at higher levels, suggesting that protein measured by the ELISA assay was fully functional, similar to previously published findings [11].…”
Section: Discussionsupporting
confidence: 90%
“…Emerging and existing therapies for FXIII-deficiency with recombinant FXIII or factor concentrates would benefit from widespread availability of FXIII activity monitoring assays with improved performance characteristics (6). Ajzner and Muszbek suggested an elegant method in which they correct test results of NAD(P)H-based FXIII activity assays by plasma blanks that reflect the activity of NAD(P)H-degrading enzymes present in the plasma matrix (20). Thus, we set out to develop a prototype of a thio-NADH-based FXIII activity assay that could be used on virtually all coagulation analyzers.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that improvements in trueness of measurement in the lower measuring range for FXIII activity tests appear desirable (19,20). The same applies to a reduction of interferences observed in hemolyzed, icteric, and lipemic (HIL) samples.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Levente Karpati et al 42 in 2000, an overestimation of 8% occurred by Berichrom assay in which replacement of NADPH for NADH improved the results but did not omit the problem. 43 In fact, Ajzner et al stated that this overestimation is caused by NADH as a cofactor in Berichrom assay by lactate dehydrogenase in the plasma. Substitution of NADH with NADPH resolved this problem but non-specific NAD(P)H consumption remained as a source of error.…”
Section: Photometric Assaymentioning
confidence: 99%